The Role of Teachers in Enhancing Students’ Critical and Cognitive Thinking Skills - Zelia Rahmayati; Salmin Putriani; Ultri Tavia Solehah; Siti Nurul Nadia; Syaiful Alamsyah; Muhammad Sani; Sunadil Fahmi; Muhammad Fairuz (Formad English Foundation NTB-Jakarta, 2026)
The increasing demands of 21st-century education highlight the importance of developing students’ critical and cognitive thinking skills, which are essential for problem-solving, decision-making, and meaningful learning. This study aims to examine the role of teachers in enhancing these skills through a systematic analysis of existing literature. A qualitative approach was employed using a systematic literature review design. Data were collected from 25 scholarly articles published between 2015 and 2025, sourced from reputable academic databases. The selection process followed specific inclusion and exclusion criteria, and the data were analyzed using thematic analysis involving data reduction, categorization, and synthesis. The findings reveal that teachers play multifaceted roles as facilitators, designers, and motivators in fostering students’ higher-order thinking skills. In promoting critical thinking, teachers utilize student-centered strategies such as problem-based learning, project-based learning, inquiry-based learning, and structured discussions. The integration of technology and social media enhances students’ engagement and critical reflection when guided effectively. Additionally, teachers support the development of metacognitive skills through reflective activities and guided questioning. In terms of cognitive thinking, teachers design structured learning experiences, apply collaborative and analytical approaches, and use higher-order questioning to stimulate deeper understanding. Student engagement, motivation, and a supportive learning environment are key factors influencing cognitive development. In conclusion, the study emphasizes that effective teacher roles and pedagogical strategies are crucial in developing students’ critical and cognitive thinking skills. These findings contribute to the theoretical understanding of student-centered learning and provide practical implications for improving instructional practices in the digital era.